Exploring Hypertension Management Practices at Community Health Center Mojolangu Indonesia: Insights from Patient Profiles - Mutiara Titani, Akrom2,Elva Asmiati, Muhammad Alie Mansub, Khoirush Shofa Mustaqim, Ach. Ilham, Abdul Fadlil (South Eastern European Journal of Public Health, 2025)
Hypertension, often referred to as the "silent killer," represents a significant public health concern in Indonesia, contributing to an increased risk of cardiovascular disease, stroke, and kidney failure. The prevalence of hypertension in Indonesia is exceedingly high, with 34.1% of adults affected by hypertension in 2018. This study employed a cross-sectional design, utilizing general clinic registration book data and prescriptions to analyze demographic profiles, visits, and antihypertensive treatment profiles. The findings at PuskesmasMojolangu in Indonesia indicated that the majority of hypertensive patients were female (70.91%), with the highest age range being 55-64 years (35.05%) and age > 65 years (34.91%). Furthermore, the study examined the frequency of repeat visits among hypertensive patients. The majority of patients (17.66%, or 261 individuals) made a single visit, while 29.36% (217 patients) who returned to the health center for a subsequent visit had unstable blood pressure. Furthermore, the analysis revealed that the most frequently prescribed treatment profile was amlodipine, representing 66.14% of cases with a dose of 10 mg once a day. This was observed in 2125 out of 3612 prescriptions. Overall, this study provides a comprehensive insight into hypertension management in the Indonesian primary care setting, where low re-visits to health centers were found, and the most widely used treatment profile was amlodipine.